YouTube as a Source of Information on Confined Space Safety - Muise Brad; Freeman Brad; Blair Earl (Occupational Health and Safety Society of Nepal, 2012)
afety professionals looking for information on confined space safety often use the Internet as a resource. YouTube is a popular website that may be used to supplement safety training or as a source of information pertaining to Confined Spaces (CS). YouTube was examined as a source of information on CS safety. YouTube was queried using key phrases "confined space," "confined space entry," and "confined space rescue." Two safety experts reviewed each video and assigned score for accuracy and view-ability. Of the 220 videos screened, 48 were found to have relevant information about CS safety and were selected for inclusion in the study. Approximately 70.8% of the videos were rated as inaccurate and 87.5% were rated as offering little value. Results of our study suggest that YouTube may currently be an inadequate source of information on CS safety. Safety professionals should verify YouTube video content against trusted agencies such as OSHA before using them as a resource for CS information